Pengembangan Bahan Ajar Hikayat Berbantuan Media Renderforest untuk Meningkatkan HOTS Siswa Kelas X SMK Negeri 1 Patumbak - Batubara, Khairunnisa; Andriany, Liesna; Kartika, Rika (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2024)
This study aimed to develop folklore teaching materials (sagas/hikayat) assisted by Renderforest media to improve the thinking skills of students in class X PPLG 1, X PPLG 2, and X BDP 1 at SMK Negeri 1 Patumbak. Using a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), data were collected through observations and questionnaires. The results showed that the teaching materials for folk tales (saga) assisted by Renderforest media were rated "Very Eligible" (97%) by media experts and "Decent" (76%) by teachers. A field test with 66 students from class X PPLG 2 demonstrated the effectiveness of the teaching materials, with activity tests and evaluations yielding an "effective" rating (81%). These findings suggest that integrating Renderforest media into folklore teaching materials can significantly enhance students' higher-order thinking skills (HOTS). Further research is recommended to explore the long-term impacts of these teaching materials on students' learning outcomes across different subjects and grade levels.